Transcription Factor CsWIN1 Regulates Pericarp Wax Biosynthesis in Cucumber Grafted on Pumpkin - Zhang, Jian; Yang, Jingjing; Yang, Yang; Luo, Jiang; Zheng, Xuyang; Wen, Changlong; Xu, Yong (Frontiers in Plant Science, 2019)
Pericarp wax of cucumber is an important economic trait, determining sales and marketing. Grafting of cucumber onto pumpkin rootstock (Cucurbita moschata) is an effective way to produce glossy cucumber fruits. However, the molecular regulation mechanism of this phenomenon remains largely unknown. In the present study, transcriptome analyses, genome-wide DNA methylation sequencing, and wax metabolite analysis were performed on the pericarp of self-rooted versus grafted cucumber. We identified the AP2/ERF-type transcription factor CsWIN1 as methylated and significantly upregulated in grafted cucumber compared to self-rooted cucumber. The increased expression of CsWIN1 was also positively correlated with several key wax biosynthesis genes, including CsCER1, CsCER1-1, CsCER4, CsKCS1, and the wax transporter gene CsABC. The transcriptome expression level of these genes was validated through qRT-PCR profiles. Furthermore, wax metabolite analysis showed that more wax ester (C20 fatty acid composition), but fewer alkanes (C29 and C31) were deposited in grafted cucumber pericarp. The higher expression of CsWIN1 and wax biosynthesis genes was reflected in the glossier appearance of grafted pericarp, possibly the result of higher wax ester content and higher integration of small trichomes in the pericarp. This study demonstrates that grafting can affect the content and composition of pericarp wax in cucumber grafted on pumpkin, and a unique regulation model of CsWIN1 for wax biosynthesis may exist in cucumber.